1989
DOI: 10.1002/dc.2840050406
|View full text |Cite
|
Sign up to set email alerts
|

Ductal carcinoma‐in‐situ of the breast: Fine‐needle aspiration cytology of 12 cases

Abstract: Aspiration specimens from 12 patients with histologically documented ductal carcinoma-in-situ (DCIS) of the breast (seven patients) or DCIS with minute foci of stromal invasion (five) were evaluated. Five patients presented with palpable masses, 1.5-4.0 cm, and four patients presented with localized thickening, associated with nipple erosion and discharge in two of them. One patient had nipple inversion, and one patient had bilateral nipple discharge. In one patient, no apparent abnormality of the breast was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 21 publications
2
10
1
Order By: Relevance
“…Overall, 48% of DCIS aspirates in our study contained necrosis. As previously reported, 5,14 rare cases of low grade DCIS also can contain necrosis, but findings by one group of investigators contradicted this. 15 However, the majority of reports regarding the cytologic features of DCIS in the literature suffer from limited sample size and the majority of cases being high grade carcinoma with necrosis.…”
Section: Discussioncontrasting
confidence: 38%
See 3 more Smart Citations
“…Overall, 48% of DCIS aspirates in our study contained necrosis. As previously reported, 5,14 rare cases of low grade DCIS also can contain necrosis, but findings by one group of investigators contradicted this. 15 However, the majority of reports regarding the cytologic features of DCIS in the literature suffer from limited sample size and the majority of cases being high grade carcinoma with necrosis.…”
Section: Discussioncontrasting
confidence: 38%
“…In our series, 61% of DCIS specimens had scores Ͼ 2ϩ for dissociated single cells, a finding that is in agreement with previous studies that reported no significant difference in the number of dissociated single cells between IDC and DCIS aspirates. 5,11,15 Many single cells also can be observed in atypical ductal hyperplasia and ductal hyperplasia mimicking low grade carcinoma. 6 It has been suggested that the presence of tumor cells infiltrating adipose tissue might be an indication of local stromal invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies available highlighting the cytologic features employed in evaluating these lesions. 1,4,6,[8][9][10][11] The features stressed include the presence of nuclear overlap; swirling three-dimensional masses with outlying myoepithelial cells and sublumens; small, frayed groups of ductal cells; and alterations in nuclear size and chromatin texture. There is disagreement about whether atypical ductal hyperplasia can be distinguished from ductal carcinoma in situ and the latter from infiltrating carcinoma on fine needle aspiration (FNAC) smears.…”
Section: Objective: To Determine the Usefulness Of Fine Needle Aspiramentioning
confidence: 99%